THE INFLUENCE OF PERCEIVED EASE OF USE AND PERCEIVED RISK ON THE DECISION TO USE THE GOPAY APPLICATION IN MEDAN CITY - Simangunsong, Maria Meilani; Simanjorang, Feronica (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
The potential impact of perceived ease of use and perceived risk on a user's choice to either continue using or switch from the Gopay app is being investigated in this study. The main objective of this research is to establish how perceived ease of use and perceived risk affect the decision to use the Gopay app within Medan City. This study utilises a quantitative research methodology with an associative perspective. The target population for this research consists of Gopay app users in Medan City, and the sample size is 96 respondents, selected using purposive sampling. Obtaining primary data involved directly distributing questionnaires, while secondary data was collected through studying literature. The findings of the study indicate that beliefs about how easy it is to use and the level of risk perceived both have a significant and positive impact, either partially or together, on the decision to utilise the Gopay application in Medan City. The Adjusted R Square value, at 0.846 or the determinant coefficient, underscores that the variables of perceived ease of use (X1) and perceived risk (X2) in relation to the decision to use (Y) account for 84.6% of the variance, with the remaining 15.4% influenced by factors not considered in this research model.